Gastrointestinal helminth parasitism in fruit-eating bats (Chiroptera, Stenodermatinae) from western Amazonian Brazil - Nogueira, Marcelo R; de Fabio, Sueli P; Peracchi, Adriano L (Revista de Biología Tropical, 2004)
In this paper we report endoparasites from a sample of 50 stenodermatine bats collected mainly over lick sites at the Parque Nacional da Serra do Divisor, westernmost extremity of Amazonian Brazil. Four helminth species were recovered (Hasstilesia tricolor, Vampirolepis elongatus, Cheiropteronema globocephala, and Capillaria sp.), most of them from small intestines. Overall helminth prevalence achieved 26% (13/50) and the more prevalent species was H. tricolor (20%). Previously unknown in bats and reported for the first time in Brazil, this digenetic trematode was found in seven of the 18 bat species studied here. We argue that the drinking behaviour of stenodermatines at lick sites may be implicated in the dissemination of helminth infection among these bats.